Epithelioid and Spindle Cell Hemangioma: Clinicopathologic Analysis of 18 Primary Bone and Soft Tissue Tumors Highlighting a Predilection for the Hands and Feet, Frequent Multicentricity, and Benign Behavior. (10th October 2022) - Papke, David J.; Jagannathan, Jyothi; Dong, Fei; Dickson, Brendan C.; Mertens, Fredrik; Hornick, Jason L.; Fletcher, Christopher D.M.
Abstract : Epithelioid and spindle cell hemangioma was initially described in 1999 in a series of primary bone tumors and was subsequently suggested by some to represent a variant of epithelioid hemangioma. Here, we studied 18 epithelioid and spindle cell hemangiomas. Nine patients (50%) were male. Age at presentation ranged from 12 to 78 years (median: 38.5 y). Nine patients (50%) had tumor(s) limited to bone, 5 (28%) had tumor(s) limited to soft tissue, and 4 (22%) had tumor(s) involving bone and soft tissue. Nine patients (50%) had multiple tumors, all in a unilateral anatomic region involving the wrist, hand, ankle, or foot. Seventeen tumors (94%) occurred in an extremity, including 12 (67%) in the hands and feet, and 1 occurred in a vertebra. In imaging studies, primary bone tumors were lobulated, expansile, and lytic, and 7 bone tumors with available imaging (58%) showed cortical breakthrough. Tumor sizes were 0.8 to 7.2 cm (median: 2.2 cm). Epithelioid and spindle cell hemangioma is composed of lobules of epithelioid and spindled endothelial cells with bland, vesicular nuclei. Neoplastic cells show orderly vasoformative growth, with hemorrhagic stroma and no endothelial atypia or multilayering. Immunohistochemistry demonstrated uniform positivity for CD31 and ERG. Where positive, SMA highlighted pericytes (11/13 tumors). FOSB was strongly positive in 4 of 16 tumors (25%), and FOS was strongly positive in 5 of 10 stained tumors (50%). Break-apart fluorescence in situ hybridization confirmed the presence of FOS split signals in 4 tumors positive for FOS by immunohistochemistry and FOSB split signals in 2 FOSB-positive tumors. DNA sequencing demonstrated a GATA6 :: FOXO1 fusion in 1 of 3 sequenced tumors. Clinical follow-up was available for 15 patients (83%; range: 5 mo to 11 y; median: 3.5 y). Seven patients (47%) had no evidence of disease at most recent follow-up. Seven of 13 patients (54%) who underwent surgery experienced local recurrence at the primary tumor site: 5 patients within a year, 1 at 2.4 years, and 1 thrice at 2, 3, and 5 years. Six patients were alive with multifocal disease (median: 3.5 y; range: 5 mo to 6 y). No tumors gave rise to distant metastases. The clinicopathologic and genetic findings in this study support the notion that epithelioid and spindle cell hemangioma is a morphologic variant of epithelioid hemangioma that can occur in soft tissue as well as bone and that shows a striking predilection for the extremities. Given that most recurrences and primary tumors behaved indolently, watchful waiting would be reasonable for patients with multicentric disease that is not readily amenable to surgery.